Effect of Optimized Emergency Care on Treatment Rate and Prognosis of Elderly Patients with Acute Stroke in Emergency Department: A Systematic Review and Meta-Analysis - Liang, Xia; Yu, Yanhong (Computational and mathematical methods in medicine, 2022)
Objective. This research was to detect the treatment rate and prognosis of elderly patients with acute stroke in emergency department by the optimization of emergency care applying meta-analysis. Methods. The online databases including PubMed, EMBASE, ScienceDirect, Cochrane Library, China knowledge Network Database (CNKI), China VIP Database, Wanfang Database, and China Biomedical Literature Database (CBM) were searched. The retrieval time limit was set from the establishment of the database to the present. The data were extracted independently by two investigators. The bias of per publication was assessed following Cochrane manual 5.1.0 standard. RevMan5.4 statistical software was used to analyze the collected data by meta. Results. The 8 randomized controlled trials included in this meta-analysis all reported patients’ baseline status. The meta-analysis of the rescue time of the study group and the control group (CH2=1507.80, df=4, P≤0.001, and I2=100%) showed that the emergency nursing with optimized emergency procedures can shorten the rescue of elderly acute stroke patients in the emergency department time. There are 6 literatures reporting the case fatality rate (Chi2=1.12, df=5, P=0.95>0.05, and I2=0%), and the death rate of the study group was not higher than that of the control group (Z=4.4 and P<0.0001). The use of optimized first aid can reduce mortality in elderly patients with acute stroke. Six articles on disability rate reported the heterogeneity of disability rate (CH2=2.88, df=5, P=0.72>0.05, and I2=0%), indicating that the disability rate in the study group was lower than that in the control group (Z=3.91 and P<0.0001), indicating that emergency nursing by optimizing emergency procedures can reduce the disability rate of elderly stroke patients in emergency department. Conclusion. Optimizing the emergency care process can effectively improve the emergency rate and prognosis of elderly patients with acute stroke in emergency department; however, further research with higher methodological quality and longer intervention time are needed to verify later.